Progression of Gastric Acid Production in Preterm Neonates: Utilization of In-vitro Method - Palla, Murali R.; Harohalli, Shashidhar; Crawford, Tim N.; Desai, Nirmala (Frontiers in Pediatrics, 2018)
Background: There have been limited studies done regarding ability to produce gastric acid in preterm infants. Most studies have used in vivo method of assessing gastric pH. Objectives: The objectives of the study was to assess the feasibility of using an in vitro method of measuring gastric pH in babies ≤ 28 weeks gestational age (GA) and determine whether changes in gastric pH differ with gestational age, mode of delivery, and use of antenatal steroids. Design/Methods: Prospective study that enrolled extremely low birth weight (ELBW) babies. Gastric aspirate was collected before feeding. In vitro testing of gastric aspirates for pH were done on days of life 1, 3, 5, 7, 14, and 28 by using pH electrode. The pH was measured on each sample in triplicate and the mean calculated and used for data analysis. Stastical methods included descriptive statistics, t-tests and repeated measures ANOVA. Results: 29 subjects were enrolled. All were ≤ 28 weeks or had birth weight ≤ 1000 g. The first feeding occurred at mean day of life 3. No significant change was noted in pH measurements over time. (Mean Coefficient of variation - 1.16%). Antenatal steroids and mode of delivery did not affect gastric acid pH. Conclusion: The invitro method for gastric pH measurements is noninvasive and affords more frequent testing. It would be useful in studying various conditions that may affect gastric pH.